Women in Europe between the wars : politics, culture and society - Kershaw, Angela; Kimyongür, Angela (Ashgate, 2007)
This volume's central assertion is that the 'forgetting' of European women's contributions during the period between the two world wars was not accidental but was ideologically motivated. Key concerns are canon formation. genre, literature and journalism, women's political activism, antifascism, the avant-garde, professional life, and women's involvement in voluntary associations. Bringing together scholars with diverse expertise, the collection invites connections and comparisons across the whole spectrum of women's political, social, and cultural activities.